Effects of Pazopanib Monotherapy vs. Pazopanib and Topotecan Combination on Anaplastic Thyroid Cancer Cells - Di Desidero, Teresa; Orlandi, Paola; Gentile, Daniela; Bocci, Guido (Frontiers in Oncology, 2019)
The aim of this study was to determine the activity of the combination pazopanib/topotecan vs. pazopanib monotherapy on anaplastic thyroid cancer (ATC) cells. Proliferation assays were performed on ATC cell lines exposed for 72 h to pazopanib and topotecan alone and to their simultaneous combination. Pazopanib and topotecan caused a strong synergism on ATC cells, quantified by the combination index, increasing the intracellular concentrations of topotecan lactone measured by high-performance liquid chromatography. Moreover, through real time PCR experiments, a greatly decrease of the gene expression of ATP-binding cassette transporter G2 (ABCG-2), vascular endothelial growth factor (VEGF), hypoxia-inducible factor-1α (HIF-1α) and colony stimulating factor-1 (CSF-1) was shown in combination-treated ATC cells. In conclusion, the simultaneous combination of pazopanib and topotecan demonstrated a highly synergistic ATC antiproliferative activity, suggesting a possible and rapid translation of this schedule into clinical trials.